Case Report: The Role of Rehabilitation Program for Patients with Right Hemiparesis and Aphasia - Indriasari, Marina (KnE Social Sciences, 2024)
The neurological condition aphasia is brought on by injury to the area of the brain involved in language. The primary indicators of this disease include trouble understanding speech, having trouble expressing oneself verbally, and having trouble reading and writing. By assisting the patient in making the most of their residual language skills, recovering as much language as possible, compensating for language deficits, and learning other forms of communication, aphasia therapy aims to enhance each patient’s capacity for communication. We reported a 49-year-old male with main complaint of weakness on the right extremity and communication disorders, such as right hemiparesis, hypesthesia, and spasticity. There were perceptual and cognitive dysfunction with MMSE score = 6 accompanied by apraxia, no gross visual deficits, and no agnosia. Communication was not fluent, comprehension was good, and repetition was poor. Intensive language therapy should be initiated as soon as possible and adapted to the patient’s individual needs, medically and neurologically stable even with a delay of up to 6 months post onset. Rehabilitative programs may involve speech therapy to relearn speech and swallowing, occupational therapy to regain arm and hand dexterity, and physical therapy to improve strength, endurance, and mobilization. Speech rehabilitation involves extensive practice reading, writing, following directions, and repeating what they hear. Computer-assisted therapy can complement standard language therapy. The goal of aphasia treatment is to enhance a person’s capacity for communication by assisting them in making the most of their residual talents, regaining as much language as they can, compensating for language deficits, and learning other forms of expression. Keywords: rehabilitation program, right hemiparesis, aphasia